Communication skills required by auditors. - Ho, Alexia Wen Tsi. (2008)
It is generally felt by audit practitioners that accountancy graduates entering the profession are deficient in their communication abilities. Much criticisms have been made regarding their tendency to write at great length and yet fail to put their ideas across to the reader. Employers have also complained about graduates' inability to speak confidently and fluently. The aim of our project is to verify practitioners' perception that communication skills are crucial and to identify the specific skills needed.